ETIKA MURID TERHADAP GURU PERSPEKTIF KITAB BIDAYATUL HIDAYAH KARYA AL-GHAZALI: Etika, Murid, Guru dan Kitab Bidayatul Hidayah - Jainal Abidin (Jurnal Paradigma, 2022)
Strengthening ethical values ??in the educational process is relevant to overcoming the moral crisis that is happening in society. One of the leaders of Islamic education who made a major contribution to students is Al-Ghazali in the book Bidayatul Hidayah, ethics of students towards teachers according to Al Ghazali in the book Bidayatul Hidayah includes 13 kinds of ethics, namely greeting the teacher first, not speaking much in front of the teacher, not speaking in front of the teacher before being asked, not asking before asking permission, not arguing with the teacher, not blaming the teacher's opinion, not whispering when the teacher is delivering the lesson, not turning to the right and left in front of the teacher, not asking the teacher when the teacher is who are tired, salute when the teacher stands up, don't ask the teacher when the teacher has left the assembly, don't ask the teacher in the middle of the road, don't think badly of the teacher when he sees that his outward actions are not in accordance with the knowledge being studied